Association of Menopausal Status, Expression of Progesterone Receptor and Ki67 to the Clinical Response to Neoadjuvant Chemotherapy in Luminal Breast Cancer - Leonardo Roberto da Silva; Renato Flora Vargas; Júlia Yoriko Shinzato; Sophie Françoise Mauricette Derchain; Susana Ramalho; Luiz Carlos Zeferino
Abstract Objective To identify the biomarkers of response to neoadjuvant chemotherapy in early luminal breast cancer. Methods A cross-sectional study that included all patients with early or locallyadvanced luminal breast cancer submitted to neoadjuvant chemotherapy between 2013 and 2014. Demographic, clinic and pathologic data were retrieved from patient records. The expressions of the estrogen receptor (ER), the progesterone receptor (PR), and Ki67 were analyzed by immunohistochemistry (IHC). The status of the human epidermal growth factor receptor 2 (HER2) was evaluated by IHC and fluorescent in situ hybridization (FISH). Independent predictors of clinic and pathologic response were evaluated by stepwise logistic regression models and receiver operating characteristic (ROC) curve analysis. Results Out of 298 patients identified, 115 were included in the analysis. Clinical complete response (cCR) was observed in 43.4% of the patients (49/113), and pathologic complete response (pCR) was observed in 7.1% (8/115) of the patients. The independent predictors of cCR were premenopausal status (p < 0.001), low PR expression (≤ 50% versus > 50%; p = 0.048), and Ki67 expression ≥ 14% (versus < 14%; p = 0.01). Patients with cCR were more commonly submitted to breast conserving surgery (34.7% versus 7.8%; p < 0.001). Increasing cut-off points for Ki67 expression were associated with an increase in specificity and a decrease in sensitivity to identify patients with cCR. Conclusion Premenopausal status, lower PR expression and higher Ki67 expression were associated with a higher rate of cCR to neoadjuvant chemotherapy in luminal breast cancer.